Gender and Plant Health Webinar Series: Lessons learned and the way forward - Gender and Plant Health Research Network (2025)
This report summarizes lessons from the Gender and Plant Health Webinar Series (2024–2025), which explored how gender and social inclusion influence the design, adoption, and impact of plant health innovations. Drawing on 16 webinars and case studies from Africa, Asia, and Latin America, the report shows that plant health interventions—such as integrated pest management and digital decision-support tools—often produce unequal outcomes when gender and social dimensions are overlooked. Persistent barriers related to access to technology, extension services, resources, and decision-making power limit women farmers’ ability to benefit from these innovations. The findings highlight the importance of interdisciplinary collaboration and gender-responsive research design to achieve equitable, effective, and sustainable plant health outcomes, contributing to resilient agrifood systems and inclusive food security.